Autophagy: the misty lands of Chlamydia trachomatis infection - Zhang, Shan; Jiang, Yufei; Yu, Yonghui; Ouyang, Xuan; Zhou, Dongsheng; Song, Yajun; Jiao, Jun (Frontiers in Cellular and Infection Microbiology, 2024)
Chlamydia are Gram-negative, obligate intracellular bacterial pathogens that infect eukaryotic cells and reside within a host-derived vacuole known as the inclusion. To facilitate intracellular replication, these bacteria must engage in host-pathogen interactions to obtain nutrients and membranes required for the growth of the inclusion, thereby sustaining prolonged bacterial colonization. Autophagy is a highly conserved process that delivers cytoplasmic substrates to the lysosome for degradation. Pathogens have developed strategies to manipulate and/or exploit autophagy to promote their replication and persistence. This review delineates recent advances in elucidating the interplay between Chlamydia trachomatis infection and autophagy in recent years, emphasizing the intricate strategies employed by both the Chlamydia pathogens and host cells. Gaining a deeper understanding of these interactions could unveil novel strategies for the prevention and treatment of Chlamydia infection.